Evaluation of the speed of a complex visual-motor response in highly skilled female boxers - Коробейніков, Георгій Валерійович; Коробейніков, Г. В.; Коробейников, Георгий Валерьевич; Korobeinikov, Heorhii V.; Korobeynikov, Georgiy; Штанагей, Дмитро Вікторович; Штанагей, Д. В.; Штанагей, Дмитрий Викторович; Shtanahei, Dmytro V.; Shtanagey, Dmytriy; Єременко, Наталія Петрівна; Єременко, Н. П.; et al. (Universitatea din Pitesti, 2020)
Purpose: determining the peculiarities of complex visual-motor response of female boxers with different types of functional asymmetry. Material: 50 highly skilled female boxers (masters of sports of international class, masters of sports). The study of female boxer psychomotor functions was designed according to a certain scheme. The motor component of motor response was examined by means of tapping test. The time of a simple and two complex visual-motor responses was determined. The study was completed by determining the identification time for visual stimuli of various degrees of complexity without a motor response. It was assumed that this will allow to consider the visual-gnostic component in a "pure" form. Such a design of the study permitted to evaluate the contribution of each component of psychomotor response to the response speed of female boxers with different types of functional hemispheric asymmetry (FHA) profile. Results:the right hand of the right-handers was found to be significantly faster than that of left-handers and, especially, ambidexters. The left hand speed of the right-handers is almost the same as that of the left-handers, whereas in ambidexters it is significantly higher. The right-handers appear to be faster during realization of complex visual-motor response than both the left-handers and ambidexters. As for the asymmetry of the legs, it is not possible to talk about the relationship between the lateralization character and the speed of the choice time. Among most of athletes the right-legged (60.0%) and the left-legged (75.0%) were in the group with a high speed of response. Conclusions:A comparison of the responses to the stimulus of the two alternatives shows that the right hand of right-handers is significantly faster than that of the left-handers and, especially, ambidexters. The speed of the left hand of the right-handers is almost the same as that of the left hand of the left-handers, and only in ambidexters it is much higher. Comparison of the responses to the stimulus of the three alternatives indicates that both the right hand and the left hand of the right-handers are significantly faster than those of athletes of the other two groups.Right-handers tend to be faster than left-handers and ambidexters during realization of a complex visual-motor response. The time of complex response in highly skilled female boxers is associated with visual lateralization. Athletes with the right dominant eye are more "speedy".

Мета: визначити особливості складної зорово-моторної реакції жінок-боксерів з різними типами функціональної асиметрії. Матеріал: 50 висококваліфікованих жінок-боксерів (майстри спорту міжнародного класу, майстри спорту). Вивчення психомоторних функцій жінок-боксерів було розроблено за певною схемою. Руховий компонент рухової реакції досліджували за допомогою методу тепінг-тестування. Був визначений час простої та двох складних зорово-моторних реакцій. Дослідження завершили визначенням часу ідентифікації зорових подразників різного ступеня складності без рухової реакції. Передбачалося, що це дозволить розглядати візуально-гностичний компонент у "чистому" вигляді. Така конструкція дослідження дозволила оцінити внесок кожного компонента психомоторної реакції у швидкість реакції жінок-боксерів з різними типами профілю функціональної півсферичної асиметрії (FHA). Результати: виявилось, що права рука правшів значно швидша, ніж рука лівшів і, особливо, амбідекстерів. Швидкість лівої руки у правшів майже така ж, як і у лівшів, тоді як у амбідекстерів вона значно вища. Правші виявляються швидшими під час реалізації складної зорово-рухової реакції, ніж і лівші, і амбідекстри. Що стосується асиметрії ніг, то не можна говорити про взаємозв'язок між характером латералізації та швидкістю певного часу. Серед більшості спортсменів правоногі (60,0%) та лівоногі (75,0%) були у групі з високою швидкістю відповіді. Висновки: Порівняння реакцій на стимул двох альтернатив показує, що права рука правшів значно швидша, ніж рука лівшів і, особливо, амбідекстерів. Швидкість лівої руки правшів майже така ж, як і швидкість лівої руки лівшів, і лише у амбідекстерів вона набагато вища. Порівняння відповідей на стимул трьох альтернатив свідчить про те, що як права, так і ліва рука правшів значно швидші, ніж у спортсменів інших двох груп. Правші, як правило, швидші, ніж лівші та амбідекстери під час реалізації складної зорово-моторної реакції. Час складної реакції у висококваліфікованих жінок-боксерів пов'язаний із зоровою латералізацією. Спортсмени з правим домінантним оком більш "швидкісні".

Цель: определить особенности сложной зрительно-моторной реакции женщин-боксеров с различными типами функциональной асимметрии. Материал: 50 высококвалифицированных женщин-боксеров (мастера спорта международного класса, мастера спорта). Изучение психомоторных функций женщин-боксеров был разработан по определенной схеме. Двигательный компонент двигательной реакции исследовали с помощью метода теппинг-тестирования. Было определено время простоя и двух сложных зрительно-моторных реакций. Исследование завершили определением времени идентификации зрительных раздражителей различной степени сложности без двигательной реакции. Предполагалось, что это позволит рассматривать визуально-гностический компонент в "чистом" виде. Такая конструкция исследования позволила оценить вклад каждого компонента психомоторной реакции на скорость реакции женщин-боксеров с разными типами профиля функциональной полусферической асимметрии (FHA). Результаты: оказалось, что правая рука правшей значительно быстрее, чем рука левшей и особенно амбидекстеров. Скорость левой руки у правшей почти такая же, как и у левшей, тогда как у амбидекстеров она значительно выше. Правши оказываются быстрее при реализации сложной зрительно-двигательной реакции, чем и левши, и амбидекстеры. Что касается асимметрии ног, то нельзя говорить о взаимосвязи между характером латерализации и скоростью за определенное время. Среди большинства спортсменов правоногие (60,0%) и левоногие (75,0%) были в группе с высокой скоростью ответа. Выводы: Сравнение реакций на стимул двух альтернатив показывает, что правая рука правшей значительно быстрее, чем рука левшей и особенно амбидекстеров. Скорость левой руки правшей почти такая же, как и скорость левой руки левшей, и только у амбидекстеров она гораздо выше. Сравнение ответов на стимул трех альтернатив свидетельствует о том, что как правая, так и левая рука правшей значительно быстрее, чем у спортсменов двух других групп. Правши, как правило, быстрее, чем левши и амбидекстеры при реализации сложной зрительно-моторной реакции. Время сложной реакции в высококвалифицированных женщин-боксеров связан со зрительной латерализацией. Спортсмены с правым доминантным глазом более «скоростные».
Korobeynikov G. Evaluation of the speed of a complex visual-motor response in highly skilled female boxers / G. Korobeynikov, D. Shtanagey, N. Ieremenko, V. Aksiutin, T. Danko, et al. // Journal of Physical Education and Sport. – V. 20 (4). – Universitatea din Pitesti, 2020. – P. 1734-1739.
Keywords: boxing; functional asymmetry; psychophysiological functions; sensomotorics; technical preparedness; бокс; функціональна асиметрія; психофізіологічні функції; сенсомоторика; технічна підготовленість; бокс; функциональная асимметрия; психофизиологические функции; сенсомоторика; техническая подготовленность; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Sports